Age‐Specific Associations Between Systolic Blood Pressure and Cardiovascular Disease: A 10‐Year Diabetes Mellitus Cohort Study. Issue 14 (21st July 2020) - Wan, Eric Yuk Fai; Yu, Esther Yee Tak; Chin, Weng Yee; Wong, Ian Chi Kei; Chan, Esther Wai Yin; Chen, Shiqi; Lam, Cindy Lo Kuen
Abstract : Background: The relationship between systolic blood pressure (SBP) and cardiovascular disease (CVD) among patients with diabetes mellitus remains unclear. The study aimed to explore age‐specific associations between SBP and CVD. Methods and Results: A population‐based retrospective cohort study was conducted on 180 492 Chinese adults with type 2 diabetes mellitus in 2008–2010, with follow‐up to 2017. Age‐specific associations (<50, 50–59, 60–69, and 70–79 years) between the average SBP in the previous 2 years and CVD risk were assessed by adjusted Cox proportional hazards regression with age‐specific regression dilution ratios and patient characteristics stratified by subgroups. During a median follow‐up of 9.3 years (1.5 million person‐years), 32 545 patients developed a CVD, with an incidence rate of 23.4 per 1000 person‐years. A positive and log‐linear association between SBP and CVD risk was observed among the 4 age groups without evidence of a threshold down to 120 mm Hg, but the magnitude of SBP effect on CVD attenuated with increased age. The CVD risk in the age group <50 years was ≈22% higher than the age group 70 to 79 years (hazard ratio [HR], 1.33 [95% CI, 1.26–1.41] versus HR, 1.09 [95% CI, 1.07–1.11]). Each 10‐mm Hg higher SBP was associated with 12% (HR, 1.12 [95% CI, 1.10–1.13]), 11% (HR, 1.11 [95% CI, 1.10–1.13]), and 20% (HR, 1.20 [95% CI, 1.17–1.22]) higher risk of all composite CVD events, individual CVD, and CVD mortality, respectively. Conclusions: There is a significant log‐linear relationship between baseline SBP and the risk of CVD among patients with diabetes mellitus in China. The risk increases from an SBP of 120 mm Hg onward. Age influences this relationship significantly, with younger patients (<50 years) having a greater risk of CVD for a similar rise in SBP as compared with those who are older. These findings suggest that differential target blood pressures stratified by age maybe useful.